1965
DOI: 10.1002/app.1965.070090405
|View full text |Cite
|
Sign up to set email alerts
|

The mechanical fatigue limit for rubber

Abstract: Investigations of the dynamic cut growth behavior of vulcanized rubbers indicate that there is a minimum tearing energy at which mechanical rupture of chains occurs. The limiting value is characteristic of each vulcanizate, but is in the region of 0.05 kg./cm. The mechanical fatigue limit, below which the number of cycles to failure increases rapidly, is accurately predicted from this critical tearing energy. Characteristics of cut growth at low tearing energies, and effects of polymer, vulcanizing system, oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
155
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(162 citation statements)
references
References 10 publications
7
155
0
Order By: Relevance
“…2a and 2b is quickly lost as the polymer strongly binds with the filler particles, and the composite's mechanical strength is likewise forfeited. 18 Similarly, as the AB content increases in the AB/PVDF composites, the pure polymer phase shrinks due to the formation of the fixed polymer layer on the AB. At the higher AB content of 1:1 AB:PVDF, all of the PVDF is associated with fixed polymer layers on AB particles.…”
Section: Resultsmentioning
confidence: 99%
“…2a and 2b is quickly lost as the polymer strongly binds with the filler particles, and the composite's mechanical strength is likewise forfeited. 18 Similarly, as the AB content increases in the AB/PVDF composites, the pure polymer phase shrinks due to the formation of the fixed polymer layer on the AB. At the higher AB content of 1:1 AB:PVDF, all of the PVDF is associated with fixed polymer layers on AB particles.…”
Section: Resultsmentioning
confidence: 99%
“…A peculiar attention has been paid to the quasi equilibrium properties which could be deduced from the network theory and the theory of entropic elasticity applied to quasi ideal networks in which the length distribution of elastically active chains (EAC) would be unimodal. In such cases, a key characteristic is the number of chains crossing a unit area in unloaded state [4]; according to Lake [5], there is a simple relationship with the molar mass M c of EACs: (1) where G IC0 is the threshold tear strength that characterizes fracture free of viscoelastic or strain induced crystallization (SIC) effects. K is mainly related to the rupture energy of a single chain.…”
Section: Introductionmentioning
confidence: 99%
“…From studies using small-angle X-ray scattering Cutting Test and transmission electron microscopy, cylindrical Previous studies 12,13 have shown that the meadomains of PS have been observed in neat SBS sured fracture energy is significantly reduced films cast from toluene solution. 15,16 Because when a sharp blade is applied at the tip of a crack.…”
Section: Measurements Of Fracture Energymentioning
confidence: 99%